Analisis Prosedur Pemberian Kredit pada KSP Kopdit Pintu Air Cabang Koting - Fransiskus Nong Anis; Maria Nona Dince; Wihelmina Maryetha Yulia Jaeng (Universitas 45 Surabaya, 2024)
This research aimed to define the process of credit approval at KSP Kopdit Pintu Air of Koting Branch. The research method used was descriptive qualitative, with primary data as the main source. Analysis of the credit approval process was conducted through observations and interviews. The result of results indicated that the credit granting process at KSP Kopdit Pintu Air of Koting Branch consisted of several stages such as credit application, credit analysis, credit disbursement, and credit assistance. Although the credit granting process at KSP Kopdit Pintu Air of Koting Branch had been generally effective, principle of granting credit based on 5C had been well implemented at KSP Kopdit Pintu Air of Koting Branch was not applied to small loans.